Genetic diversity and evolutionary relationships among Legionella pneumophila clinical isolates, Portugal, 1987 to 2012 - Chasqueira, Maria de Jesus (2017)
This study was supported by the Portuguese Foundation for Science and Technology (FCT) [grant number PTDC/SAU-ESA/64269/2006].